Media studies of Central and Eastern European countries in the scientific bases of China - Lingzhi, Лай (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
This paper analyzes scientific papers on the media of Central and Eastern Europe, published in the period from December 26, 1991 to July 1, 2020 and collected in the CNKI database. Research on this aspect in Chinese scientific circles is becoming increasingly large-scale and objective and demonstrates a comprehensive and multifaceted dynamics. A huge number of scientific papers on politics, economics, culture, social structure, and diplomatic relations with these countries have appeared. The purpose of the study is to identify the volume of information recorded in the database and the directions of research on the media of these countries.